Peran Supervisi Pendidikan dalam Meningkatkan Profesionalitas Guru - Muhammad Asrori Ma'sum (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2017)
A conducive and dynamic learning can not deny the role of the teacher as an intermediary of transfer of knowledge to learners. But in reality not a few of the teachers encountered some obstacles that cause less maximal implementation of teaching and learning process. Seeing the facts and phenomena, the teacher is a teacher who is part of human resources components that must be nurtured and developed continuously in the hope to perform its functions professionally. This is where the necessary supervision of education to supervisi and improve teaching and learning process conducted by teachers. The step of the education supervisor should be more focused on how a supervisor and principal can condition the supervisid teacher to cooperate with the supervisor, because the teacher's lack of optimal teaching needs to be discussed between teacher and supervisor and principal so that input from the discussion with teachers is useful for performance improvement teacher in the future.